(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines how writers such as Mary Shelley, Charlotte and Emily Brontë, and Ann Radcliffe redefined Gothic literature as a means of female expression and resistance. Drawing on Ellen Moers’ “Female Gothic” (1976) and feminist theories by Gilbert and Gubar (1979), it explores how these authors used Gothic motifs—confinement, madness, the double, and the haunted space—to reflect women’s struggles for autonomy and identity. Through a comparative and intersectional analysis of Frankenstein, Jane Eyre, Wuthering Heights, and The Mysteries of Udolpho, the research reveals patterns of psychological conflict and moral transcendence that transformed terror into empowerment. The findings highlight how nineteenth-century women’s Gothic fiction became both an aesthetic and political platform, allowing women to challenge patriarchal norms, assert creative authority, and negotiate gender, class, and authorship. Ultimately, the study affirms that Gothic literature in women’s hands evolved into a discourse of fear and freedom—an imaginative rebellion against oppression.